Diagnostic utility of cancer ratio in differentiating malignant from non-malignant pleural effusions in a tertiary care centre in central Kerala - Nishanth, P. S.; Devassy, Thomas Vadakkan; Jose, Tessa (International Journal of Advances in Medicine, 2022)
Background: Malignant pleural effusion (MPE) is a common clinical condition observed in patients suffering from malignant diseases. None of the tumour markers have both high sensitivity and specificity. A retrospective study on patients with pleural effusion was done to evaluate the diagnostic accuracy of Cancer ratio (CR) in diagnosing MPE. Methods:A retrospective analysis of patients with undiagnosed exudative pleural effusion was done. Results of serum Lactate dehydrogenase (LDH), pleural fluid Adenosine deaminase (ADA), pleural fluid analysis such as cytology and histopathology reports of pleural biopsy were analyzed. Serum LDH: pleural fluid ADA ratio (CR) was calculated and compared with histopathology report. Data were analyzed statistically. Results: A total of 102 patients were enrolled in the study (56 males and 46 females). The sensitivity and specificity of CR at the cut off level of >20 were 57.14% and 75.47% respectively. The positive predictive value was 68.29% and the negative predictive value was 65.57%. CR>20 (p<0.001) is statistically significant in predicting malignancy in undiagnosed exudative pleural effusions. Conclusions:CR has a high sensitivity and specificity and is a novel tool in differentiating malignant from nonmalignant pleural effusions. Patients with unconfirmed diagnosis but higher CR will identify the need for early biopsy, follow-up and frequent or repeat chest imaging to assess the progression.